Goods and Services are no longer enough: A Multiple Case Study Approach to understand Experience Marketing - Baid, Pooja (2006)
In a market characterized by brand parity and increasing price competition, ingenious organisations are differentiating themselves by providing not just goods and services, but holistic experiences that engage and entertain consumers and connect them to the brand. Though a recent phenomenon, experience marketing is claimed to be the source of value creation and growth in the years to come. Since, a comprehensive framework for providing and managing experiences has not been developed, this research uses a deductive-inductive approach to integrate the contribution of individual theoreticians and then provide a better understanding through the study of real world experience marketing practices. A case study approach was adopted to uncover how goods and services are transformed to experiences by three successful organisations, Games Workshop, Build-A-Bear Workshop and Trafford Centre. The study reveals that although experience marketing has not been formally recognized, it has been successfully applied by the selected organisations. Through a thorough analysis and discussion of their marketing efforts a modified framework for customer experience management was developed that conceptualized the process into five stages, beginning with understanding the consumers needs, followed by developing an experiential platform, designing the brand experience, structuring the human interface and continuously innovating the offering. In addition, it also suggests an Experience Design Matrix that can be used to map and design the brand experience. Thus, in a nutshell, this research is a minutistic but sincere effort to advance the existing knowledge base of experience marketing.